Chemical and Physical Parameters Affecting Bacterial Pigment Production - Nasha Musa, N. (Elsevier Ltd, 2019)
Among natural pigments, pigments from microbial sources, particularly bacteria are potentially good alternative colorant as compared to synthetic pigments, as it is more environmental friendly. Hence, work on this pigment are being intensified especially in finding suitable growth conditions which will able the production of bacterial pigment to be carried out at a larger scale. This is to ensure a greater possibility of it to be used in numerous industrial field. In this study, a few bacterial growth requirements; light presence, various pH and shaking speeds were studied to identify the best growth condition for three colored bacterial pigments; violet, yellow and red bacteria. It was found that the violet bacteria produced more pigment in the presence of light and when shaken at a slower speed, with pigments yielding at 19.0 mg/ml and 24.87 mg/ml, respectively. The same goes for the red bacteria, where it is seen to produce more pigments in the presence of light and at a slower shaking speed, with pigment yields of 19.8 mg/ml and 40.4 mg/ml distinctively. This however contradicts with the production of yellow pigment which was produced in a higher volume in the absences of light and at a higher shaking speed with pigment yields of 35.4 mg/ml and 32.27 mg/ml correspondingly. On the other hand, all three colored bacteria, violet, yellow and red, yielded more pigment when grown in a more acidic condition, producing pigments of 26.73 mg/ml, 27.67 mg/ml and 27.7 mg/ml, respectively. The results obtained could be used as a reference to successfully produce bacterial pigment at a sizeable scale. Â© 2019 Elsevier Ltd.